Giving Voice to the Voiceless: A Case Study of Learners with Impairments in Lesotho Schools - Mateusi, C.M.; Naong, M.N. (Journal of Social Sciences, 2014)
Numerous studies show that learners with impairments are generally disadvantaged in their relationships with fellow learners – and some teachers – in mainstream classrooms. In Lesotho, this situation seems, arguably, to be getting worse. For this reason, the researchers chose to explore some of the difficulties that these learners have to deal with, with the aim of suggesting possible intervention measures that teachers could apply to ensure the meaningful inclusion of the learners concerned. An observation and in-depth documentary search was the basis of the data used in the compilation of the structured questionnaire – which was used to collect data from 25 conveniently sampled, impaired learners in two districts of Lesotho: Maseru and Berea. Findings show that inconsiderate and negative attitudes from fellow learners and some teachers – as well as inappropriate infrastructure – are the two dominant issues that impact negatively on impaired learners. The reconfiguration of classrooms and new teacher training approaches require not only a policy overhaul, but also a change of attitude and deliberate parental involvement, in order to remedy this situation.
Published Article
Keywords: Inclusive Education; Challenges; Lesotho; Impaired Learners; Teachers’ Role